2016
DOI: 10.1108/jedt-02-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of construction-related rework on selected Ugandan public projects

Abstract: Purpose -The purpose of this paper was to assess the magnitude of the impact of construction-related rework on selected project budgets and schedule in public building construction in Uganda. The magnitude of construction-related rework was the mean determined over construction contracts under a selected project and expressed as a percentage of the construction contract sum. Design/methodology/approach -A single case multi-unit study approach was adopted. A case study protocol was prepared that included a chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Likewise, Chang, Shih, and Choo’s (2011) study found an average of an 8.5% cost increase due to design changes in Taiwan, which concurs with Cox, Morris, Rogerson, and Jared’s (1999) claim that the cost associated with design changes was 5% to 8% in the United Kingdom. The reasons are obvious: Design change–induced rework results in a higher cost due to the further efforts of disassembling and restarting some completed works (Emuze, Smallwood, & Han, 2014; Yap, Low, & Wang, 2017), resulting in the loss of project productivity (Cooper & Reichelt, 2007) and higher wastage (Kakitahi, Alinaitwe, Landin, & Mone, 2016). These non-value-adding activities generate multiple knock-on effects that result in delays and disruptions to the construction workflow (Howick, Ackermann, Eden, & Williams, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, Chang, Shih, and Choo’s (2011) study found an average of an 8.5% cost increase due to design changes in Taiwan, which concurs with Cox, Morris, Rogerson, and Jared’s (1999) claim that the cost associated with design changes was 5% to 8% in the United Kingdom. The reasons are obvious: Design change–induced rework results in a higher cost due to the further efforts of disassembling and restarting some completed works (Emuze, Smallwood, & Han, 2014; Yap, Low, & Wang, 2017), resulting in the loss of project productivity (Cooper & Reichelt, 2007) and higher wastage (Kakitahi, Alinaitwe, Landin, & Mone, 2016). These non-value-adding activities generate multiple knock-on effects that result in delays and disruptions to the construction workflow (Howick, Ackermann, Eden, & Williams, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, various researchers have nominated construction-related factors as a significant rework causes (e.g. Enshassi et al, 2017;Raghuram & Nagavinothini, 2016;Kakitahi et al, 2016). This group consists of 11 critical factors of the rework causes, as shown in Table 9, which are ranked according to their impact, as the experts have named.…”
Section: Construction-related Factorsmentioning
confidence: 99%
“…Rework is known to contribute to waste and value losses in building design and construction (Kakitahi et al, 2013), and it has been considered as one of the key factors responsible for cost and schedule overruns in construction projects (Shibnai & Salah, 2015;Love et al, 2010;Hwang et al, 2009;Aiyetan, 2013;. According to the study by Kakitahi et al (2016), the impact of rework on project cost and schedule has been calculated to be approximately 4.53% and 8.42%, respectively. Josephson et al (2002) carried out a case study survey and reported that the cost of rework was 4.4% of the construction value, and the time spent on reworking was 7.1% of the total work time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impacts of rework, Table 4 indicates the ratings provided by the respondents. Global studies have elucidated rework as an endemic phenomenon that can significantly undermine project success and team morale (Kakitahi et. al., 2016;Love et.…”
Section: A Perceived Rework Problems and Impactsmentioning
confidence: 99%